Retrofitting computer numerical control to conventional lathe machine : a simulated approach - Garcia, Gregg R. (Animo Repository, 1994)
The machine tool is our most valuable aid in the manufacture of industrial goods. With the international situation as it is today, the quality and quantity of the goods are economically and even politically important factors in determining the status of the national economy. This fact alone is a sufficient confirmation that the machine tool is holding a key position. Today the Philippines has to import CNC or numerical controlled machines at a very expensive price (normally in millions of pesos) from other countries like Japan and Europe. There has been hardly any attempt taken in the development of CNC machines in the country. Thus, if we can make our own CNC machines, this would remove the need to import them. The project, though basic, is a powerful typical CNC program. A properly designed control system with a software-hardware link will control the movement of the lathe machine. The signals to be transmitted are programmed with the use of a simulation software written in C++. The software will allow the user to manipulate the lathe machine by inputting various parameters, such as position, codes and speed. The program likewise simulates the actual machine operations and consequently tests and runs it. The project aims to provide CNC capabilities to conventional lathe machines. In this way an economical skip is made to high technology and global competitiveness.